A geografia da cura e do sagrado: a resistência das benzedeiras no espaço urbano de Ponta Grossa - (:unkn) unknown (Universidade Estadual de Ponta Grossa, 2019)
This research aims to understand the reproduction of folk medicine in the urban space of Ponta Grossa – Paraná, through the know-how of the remaining benzidine in the city, from their ways of living and living in and with space (system of objects / actions) that agency social relations between human collectives and these with nonhumans. In this sense, we address the multiple symbolic dimensions (material and non-material) that constitute this system of traditional knowledge and practices. To this end, popular medicine is discussed in a way articulated with the relative degree of urbanization of the city of Ponta Grossa, as well as the modern elements that make up these spaces in a constant dialogue between modernity and tradition. The topic is approached from one of the emerging perspectives of Geographical Science - Health Geography - and it is advanced in terms of a plural approach to health and disease, but rather to consider the cultural and humanistic bias. Thus, within a sociology of absences and emergencies, we work with the method of oral history in order to translate the social organization of these actors in urban space through the social empowerment conferred upon them. It is observed that through this knowledge are organized microterritories that interconnected structure an urban network of reciprocity and solidarity in which flows of exchanges and distinct social values (against hegemonies) and of proximity (interpersonal dialogue) are moved. It is a new look at the urban, whose presence of geosymbols, commonly coming from a rural past, try to reflect the geographic imaginaries. The structured research in four chapters found that the resistant benzedeiras (similar to folk healer) in the urban space of Ponta Grossa continue to carry out their activities, attending an expressive number of people. Through their life histories it is realized that the action of modernity (in a broad sense) about their traditional knowledge ended up re-signifying old habits and incorporating new elements into their practices. The valorization and recognition of this tradition is one of the stakes to keep it strong, to nurture its projection over the years and to face the prejudice and discredit manifested by some social segments, besides being a powerful tool to face the crisis of the civilizing model.
Keywords: Benzedeiras; Medicina popular; Microterritorialidades; Geografia da saúde; Ponta Grossa; Benzedeiras (folk healer); Popular medicine; Microterritorialities; Geography of health; Ponta Grossa; Guérisseurs; Médecine populaire; Microterritorialités; Géographie de la santé; Ponta Grossa; CNPQ::CIENCIAS HUMANAS::GEOGRAFIA